Silver and Gold Nanoparticles Alter Cathepsin Activity In vitro - Speshock, Janice L (Springer, 2010)
Nanomaterials are being incorporated into many biological applications for use as therapeutics, sensors, or labels. Silver nanomaterials are being utilized for biological implants and wound dressings as an antiviral material, whereas gold nanomaterials are being used as biological labels or sensors due to their surface properties and biocompatibility. Cytotoxicity data of these materials are becoming more prevalent; however, little research has been performed to understand how the introduction of these materials into cells affects cellular processes. Here, we demonstrate the impact that silver and gold nanoparticles have on cathepsin activity in vitro. Cathepsins are important cellular proteases that are imperative for proper immune system function. We have selected to examine gold and silver nanoparticles due to the increased use of these materials in biological applications. This manuscript depicts how both of these types of nanomaterials affect cathepsin activity, which could impact the host's immune system and its ability to respond to pathogens. Cathepsin B activity decreases in a dose-dependent manner with all nanoparticles tested. Alternatively, the impact of nanoparticles on cathepsin L activity depends greatly on the type and size of the material.